P382 Neural mechanisms of attentional switching during distraction analgesia: A single-trial laser evoked potential study. Issue 9 (September 2017) - Stancak, Andrej; Fallon, Nicholas; Fenu, Alessandra; Kokmotou, Katerina; Soto, Vicente; Cook, Stephanie
Abstract : Objectives: Noxious stimuli capture attention and at the same time, pain is attenuated by a concurrent cognitive task. The present study aimed to elucidate the cortical mechanisms underlying diminution of pain during attentional distraction using single-trial electrocortical and subjective responses. Methods: In 24 healthy participants, a laser heat stimulus was applied to the dorsum of the left hand while subjects either viewed Rubin vase-face illusion (RVI), or focused on their pain and associated somatosensory sensations occurring on their stimulated hand. Pain-related sensations occurring on every laser stimulus were evaluated using a set of visual analogue scales. Factor analysis was used to identify the principal dimensions of pain experience. Laser evoked potentials (LEPs) were correlated with subjective aspects of pain experience on a single-trial basis using a multivariate regression model. Results: Subjects anticipated and perceived smaller pain whilst focusing on RVI than on their pain-related sensations. A positive LEP component at the vertex electrodes in the interval 294–351 ms was smaller during focusing on RVI than during focusing on the stimulated hand. The attention-related amplitude changes in LEPs were accounted for by an equivalent source dipole located in posterior cingulate cortex (PCC). Single-trial variations of source activity in PCC correlated with changes in Factor 1, representing essential aspects of pain, and inversely with both Factor 2, accounting for anticipated pain, and with the number of RVI figure reversals. Discussion: Single-trial analysis of LEPs and subjective responses to a noxious laser stimulus point to the possibility that the attentional switching during a distraction analgesia operates in PCC via three channels: 1. The pain modulation channel which affects the pain experience during the distraction by neural and functional connections of the posterior cingulate cortex with the anterior cingulate cortex. 2. The task engagement channel represented by reduction of the LEP potential in PCC in trials with a large number of RVIs. 3. The anticipation channel representing a contextual, top-down modulation of the distraction effect. Conclusions: PCC appears to mediate the attentional switching towards the pain during concurrent, distracting task. Switching between pain and non-pain task is modulated by the strength of engagement in a cognitive-perceptual task, and by the level of anticipated pain. Significance: Our findings shed light on the factors underlying distraction analgesia. The level of engagement in the non-pain task and the role of anticipation are the factors which can be boosted to strengthen the analgesia in clinical applications.